ISLAMIC LEADERSHIP CONTESTATION: EXPLORING THE PRACTICES OF CONSERVATIVE ISLAMIC MOVEMENTS IN INDONESIA - Kustiawan, Muhamad Taufik; Rasidin, Mhd.; Witro, Doli; Busni, Darti; Jalaluddin, Mufti Labib (Islam Futura, 2023)
This paper describes the political contestation in the election of leaders that has occurred in the last five years in Indonesia. Since the reformation era, conservative Islamic movements have gained wide freedom to spread Islamic political ideology such as the idea of upholding Islamic law. This was clearly seen in the 2017 Jakarta Gubernatorial Election and 2019 Presidential Election, where the conservative Islamic movement voiced practical political aspirations by involving the role of religion. The case that happened to Basuki Tjahaja Purnama (Ahok) who was suspected of committing blasphemy at the end of 2016, turned into a protest movement that held “Aksi Bela Islam I, II, III” (Action for Defending Islam I, II, III) which was able to mobilize all elements of religious organizations in Indonesia. This movement is also supported by the role of social media which adds to the massive Islamic populism movement to promote the enforcement of Islamic law through the political stage. This is a qualitative research that prioritizes bibliographic sources. The results of this study indicate that the voices of Muslims who are involved in the “Action to Defend Islam” add to the success of the conservatism process which has a dichotomy of political interests to realize religious authoritarianism by using the Qur’anic verses. However, this study also explains the characteristics of the attitudes of leaders in the history of Islamic civilization who uphold egalitarianism that does not conflict with the democratic system because the responsibility of a leader is to create prosperity and justice for all mankind.